SISTIM PUNYIMBANG ADAT LAMPUNG SAIBATIN PAKSI PAK SEKALA BEGHAK KEPAKSIAN BEJALAN DIWAY - Reki Fahlevi; Ali Imron; Maskun Maskun (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2013)
The original tribe who stayed in West Lampung region came from Sekala Beghak. The purpose of this study is to find out the social strata of Punyimbang Adat Lampung Saibatin Paksi Pak Sekala Beghak Kepaksian Bejalan Diway. The research method used is functional structural method which used documentation, observation and interview as the data collecting techniques. The result of this study showed that there are the noble strata at Saibatin people in Paksi Pak Sekala Beghak Kepaksian Bejalan Diway. The notable strata at Paksi Pak Sekala Beghak has been implemented since yore even it had ever been influenced by Hindia Belanda government which established rules based on the authority of Hindia Belanda government in Sekala Beghak, but in 1942-1998 there was no the influence of Hindia Belanda in this system and it reverted to the previous structure, then it changed again in 1999 till now with the advancing notable structure of Saibatin. Suku bangsa asli yang mendiami wilayah Kabupaten Lampung Barat berasal dari Sekala Beghak. Adapun tujuan di dalam penelitian ini adalah untuk mengetahui sistim Punyimbang Adat Lampung Saibatin Paksi Pak Sekala Beghak Kepaksian Bejalan diway. Metode yang digunakan adalah metode fungsional struktural dengan teknik pengumpulan data melalui dokumentasi, observasi dan wawancara. Hasil Penelitian menunjukan bahwa pada Paksi Pak Sekala Beghak Kepaksian Bejalan diway terdapat struktur kebangsawanan. Struktur kebangsawanan pada Paksi Pak Sekala Beghak Kepaksian Bejalan diway telah ada dan berlangsung sejak zaman dahulu bahkan sempat dipengaruhi Pemerintah Hindia Belanda dengan menetapkan aturan-aturan berdasarkan kekuasaan Pemerintah Hindia Belanda di wilayah Sekala Beghak, namun pada tahun 1942-1998 terjadi perubahan yaitu kembali ke struktural awal dan tidak dipengaruhi pemerintah hindia belanda, kemudian terjadi perubahan kembali pada tahun 1999-sekarang dengan perkembangan Struktural Kebangsawanan Saibatin. Kata kunci : lampung saibatin, paksi pak sekala beghak, punyimbang